The North American Arctic - Menezes, Dwayne Ryan (UCL Press, 2019)
The North American Arctic addresses the emergence of a new security relationship within the North American North. It focuses on current and emerging security issues that confront the North American Arctic and that shape relationships between and with neighbouring states (Alaska in the US; Yukon, Northwest Territories and Nunavut in Canada; Greenland and Russia).